Performance comparison of MVDR and LCMV beamforming algorithm in 2.3 GHz adaptive antenna system - Salem B.; Tiong S.K.; Koh S.P.; Hock G.C. (Praise Worthy Prize S.r.l, 2023)
The blind beamforming technique is employed in the broadband wireless mobile systems to enhance the cellular systems in the aspect of capacity, data rates, null steering and coverage. This paper presents two methods of beamforming algorithm; Minimum Variance Distortionless Response (MVDR) and Linear Constraint Minimum Variance (LCMV). MVDR and LCMV techniques form radiation beams based on the received weight vector of the desired signal. Simulation has been carried out to validate these two techniques. Four elements of the linear array antenna are used in our simulation program with the carrier frequency around 2.3 GHz, noise power 0.5dB, and the spacing between elements is 0.5 ?. The result of the simulation reveals that both the modes are capable of providing high output power; however direction of all the incoming sources is required, which is practically difficult to obtain. Nevertheless the MVDR beamforming, minimizes the multi-path fading problem, by adding the multi-path signal, which increases the strength of the desired signal and nullifies the interference. Overall, the MVDR technique is more accurate than the LCMV to null to find the interference source and directing radiation lobe with high power towards the desired signal. 2012 Praise Worthy Prize S.r.l.-All rights reserved.